Linking service design to value creation and service research - Andreassen, Tor Wallin; Kristensson, Per; Lervik-Olsen, Line; Parasuraman, A; McColl-Kennedy, Janet R; Edvardsson, Bo; Colurcio, Maria (International journal of service industry management, 2016)
Purpose – The purpose of this paper is to develop a framework for understanding service design and how service design relates to central concepts within service marketing. Design/methodology/approach – For companies, service design is growing in importance and has become a crucial capability to survive in the service-dominant economy. Service design increases the capacity to improve not only service experiences but also organizational design. On this premise, the authors propose a conceptual framework. Findings – By relating service design to research efforts within service marketing, dual value creation can be enhanced. As such, the conceptual framework portrays service design as an enhancer of customer experience and organizational performance. Originality/value – To the authors knowledge, service design has not been discussed in the service marketing literature. Thus, this is the first attempt to see service design in light of well-established service marketing models such as SERVQUAL and an updated version of the Service-profit-chain.